2020
DOI: 10.1177/1747954120959733
|View full text |Cite
|
Sign up to set email alerts
|

Perceived coach-created environment directly predicts high school athletes’ physical activity during sport

Abstract: Sport participation is an important means for adolescents to achieve moderate-to-vigorous physical activity (MVPA), yet most high school students including athletes do not achieve the 60-minute daily MVPA guideline. As psychosocial factors influence athlete engagement and physical activity during sport, the perceived environment created by coaches could play a role in this influence. Guided by self-determination and achievement goal theories, this four-month prospective study examined the direct and indirect e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 42 publications
(82 reference statements)
4
16
0
2
Order By: Relevance
“…We also observed a negative correlation between autonomy support from the coach and amotivation. There was, as expected, a direct positive (p<0.01) link between autonomy support from the coach and task environment [27,[42][43]. This indicates that coaches who give their players autonomy support have a better chance of creating a task environment, which encourages effort from the players.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…We also observed a negative correlation between autonomy support from the coach and amotivation. There was, as expected, a direct positive (p<0.01) link between autonomy support from the coach and task environment [27,[42][43]. This indicates that coaches who give their players autonomy support have a better chance of creating a task environment, which encourages effort from the players.…”
Section: Resultssupporting
confidence: 74%
“…Perceived autonomy support from friends is positively associated with identified regulation and intrinsic motivation [39]. Perceived autonomy support from exercise instructors positively predicts relatedness, autonomy, competence need satisfaction, and intrinsic motivation [27,42]. Research has demonstrated the value of perceived autonomy support from the coach and task-involving climate in predicting the intrinsic motivation in athletes [43].…”
Section: Introductionmentioning
confidence: 99%
“…Key Supporting Literature H1: Empowering climate is (a) positively related to psychological-need satisfaction; (b) negatively related to psychological-need thwarting [6,7,9,10,12,16,22,[27][28][29][30][31][32][33][34][35] H2: Psychological-need satisfaction is (a) positively related to autonomous motivation; (b) negatively related to non-motivation [4,10,12,22,[34][35][36][37][38][39][40] H3: (a) Autonomous motivation is positively related to well-being; (b) non-motivation is negatively related to well-being [6,29,37,38,41,42] H4: Psychological-need satisfaction mediates the relationship between empowering climate and autonomous motivation [5,10,29,35,36,43] H5: Disempowering climate is (a) positively related to psychological-need thwarting; (b) negatively related to psychological-need satisfaction [5,16,44,45] H6: Psychological-need thwarting is (a) positively related to non-motivation; (b) negatively related to auton...…”
Section: Hypothesesmentioning
confidence: 99%
“…Sports-psychology studies have examined the usefulness of predicting motivational processes and associated outcomes of considering the coach-created motivational climate [10][11][12][13][14][15][16]. These studies evaluated athletes from traditional sports like football and basketball, but recently a new type of athlete has emerged in video games.…”
Section: Introductionmentioning
confidence: 99%
“…In order to measure both the satisfaction and the frustration components of the different elements that are part of the BPN, the main tool used is the Basic psychological need satisfaction and frustration scale (BPNSFS) [5]. This scale was originally created to be used in the adult population, and context-specific adaptations are available including the work-domain [26], sports [27][28][29], or physical education [30,31]. However, a more generalized adaptation to the school context that goes beyond a specific subject or area such as physical education is still to be developed.…”
Section: Introductionmentioning
confidence: 99%